Identifikasi Konsep Matematika Melalui Aktivitas Etnomatematika Petani Sawah - Laksmi Aulia; Lia Rista (Jurnal Pendidikan Matematika:Judika Education, 2019)
The purpose of this study was to determine the mathematical concepts through ethnomatematics activities of rice farmers in the community in Blang Jrun village, North Aceh. This research is a type of qualitative research with an ethnographic approach. The subjects of this study were 8 people who work as farmers in Blang Jruen Village, North Aceh Regency. Data collection methods used were interviews, documentation and observation. The results showed that community farmers in Blang Jruen Village indirectly used ethnomatematics activities in rice farming. Ethnomatematic activities used include counting, counting and measuring activities. The most common activity in rice farmers is counting activity. In counting activities many mathematical concepts emerge by the farmers. Like addition; reduction; multiplication; division; worth comparison; and the comparison turned value. Whereas the spelling activity only appears in the mention of the vast rice fields. Measuring activity arises when estimating the distance between one crop and another and estimating the size of rice fields and yields. Conclusion, there are a lot of ethnomatematics activities in farming activities carried out by the Blang Jruen Village community in North Aceh Regency. Ethnomatematics activities include counting, counting and measuring activities. These concepts can be used as inspiration and contextual learning reference material. Keywords: Ethnomatematics Activities, Mathematical Concepts, Rice Farmers